2015
DOI: 10.1002/adsc.201500512
|View full text |Cite
|
Sign up to set email alerts
|

Recent Developments in Enantioselective Nickel(II)‐Catalyzed Conjugate Additions

Abstract: International audienceDuring the last ten years, an important number of novel highly efficient asymmetric conjugate additions of various nucleophiles to numerous acceptor-activated olefins have been developed on the basis of asymmetric nickel(II) catalysis by the very fact of the lower costs of nickel catalysts in comparison with other transition metals. These processes can be considered as one of the most powerful and reliable tools for the stereocontrolled formation of carbon-carbon bonds. Importantly, a ran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
28
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 62 publications
(30 citation statements)
references
References 228 publications
2
28
0
Order By: Relevance
“…Over recent decades, the use of asymmetric nickel catalysts has substantially evolved both in acid–base and redox catalysis456. Several examples of chiral nickel complexes that act as asymmetric catalysts have been sporadically characterized by X-ray structure analysis, opening up a window of opportunity to discuss the stereo-discrimination process in asymmetric nickel catalysis7891011121314151617.…”
mentioning
confidence: 99%
“…Over recent decades, the use of asymmetric nickel catalysts has substantially evolved both in acid–base and redox catalysis456. Several examples of chiral nickel complexes that act as asymmetric catalysts have been sporadically characterized by X-ray structure analysis, opening up a window of opportunity to discuss the stereo-discrimination process in asymmetric nickel catalysis7891011121314151617.…”
mentioning
confidence: 99%
“…Nitroalkanes are highly versatile synthetic intermediates on account of their facile α ‐alkylation reactions and interconversions to other important functional groups by various possible transformations . Therefore, catalytic diastereo‐ and enantioselective conjugate additions of carbon pronucleophiles to nitroalkenes has attracted much attention . The substrate‐controlled enantioselective Michael additions of ketones to nitroalkenes have been intensively investigated before the emergence of organocatalysts .…”
Section: Methodsmentioning
confidence: 99%
“…However, this catalytic system is limited by a relatively large catalyst loading (usually 10–20 mol%) and a long reaction time. Complementarily, organometal complexes have been recognized as attractive catalysts and received continuous and ever‐growing attention in this research area during the last decade . The combination of chiral diamine ligands with a metal such as Ni, Ca, Cu and Mn has been well investigated in asymmetric conjugate addition with nitroalkenes.…”
Section: Methodsmentioning
confidence: 99%
“…Disappointingly, the reaction of 14a with the Cu(II) complex of ( S )‐ 1a gave the product 18a in a low yield and the racemic form. The subsequent screening of metal precursors revealed that only the reaction with the complex of nickel(II) acetate tetrahydrate and (S)‐ 1a gave ( R )‐ 18a in quantitative yield and with moderate enantioselectivity 28. To further increase the ee value, we introduced an additional effective chiral environment within ( S )‐ 1a .…”
Section: Application In Ni Catalysismentioning
confidence: 99%